Analisis Kebutuhan Tenaga Kerja Menggunakan Metode WISN di Rumah Sakit PHC Surabaya - Septianingtyas Risti Anggraeni; Efri Tri Ardianto; Dony Setiawan Hendyca Putra (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
Medical record personnel is one part of the profession in the hospital. Medical record personnel also have animportant role in a patient service. Because it is responsible for the procurement of files beginning from patientregistration, assembling, coding, indexing, filling, internal or external reporting and INACBG’s. There is aproblem concerning the workload of medical records personnel at Surabaya PHC Hospital. A number ofofficers are have been resigning for the last few years, causing a reduction of a number of officers. Theworkload indirectly becomes higher and double jobs occurred. In addition, there are also found several officerswho have 2 jobs such as an outpatient coding officer become a filling officer, an inpatient coding officerbecome an information release officer and an assembling officer become a hemodialysis coding officer. Thepurpose of this study was to analyzed the needs of medical record personnel based on workload in SurabayaPHC Hospital using the WISN (Workload Indicator Staffing Need) method. A quantitative research approachwith a descriptive study design used as this research type. Respondents that used were 1 person reporting, 1person assembling, 1 person coding outpatient and 1 person filling. The results of this research were 12 ofofficers with an educational background in Medical Records. It took the addition of 1 person for the assemblingunit, 6 people for the outpatient coding unit, 2 people for the inpatient coding unit, 3 people for the filling unitand 1 person for the information release unit.